A Dialog Lintas Agama Sebagai Upaya Meningkatkan Keterlibatan Warga Negara (Civic Engagemen) dalam Menjaga Keharmonisan Bangsa - ama farida sari (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2022)
The involvement of citizens in creating a harmonious society is important in this era of globalization. However, in reality, social and religious problems are still the background to the occurrence of conflicts to this day. Citizens' concern for interacting and maintaining communication between people is expected to be able to reduce the conflict axes that exist in society and this can be done by citizens, one of which is through religious dialogue. The purpose of this study is to find out how citizen involvement through religious dialogue is able to maintain community harmony. This research is a type of qualitative research with a phenomenological approach where data collection techniques are used, namely interview techniques, documentation studies and through Focus Group Discussion (FGD) activities. Test the validity of the data by using triangulation techniques and data analysis techniques by collecting data, reducing data, presenting data and drawing conclusions.The results of the study show that interfaith dialogue carried out by the community through interfaith communities can be said to be successful in efforts to increase citizen involvement to create a harmonious community life in the current era of globalization, seeing that there are still many conflicts in several areas that are motivated by social and religious issues. Interfaith dialogue also provides knowledge of the diversity of religions and beliefs adopted by the Indonesian people, all of which aim to maintain the unity and integrity of the nation with the existing diversity. Interfaith dialogue can also be used as an alternative in increasing civic engagement by directly involving people of different religions